2014
DOI: 10.1089/tmj.2013.0279
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Pediatric Tele-echocardiography: 15-Year Experience of Over 10,000 Transmissions

Abstract: Use of IP technology at a single center corresponded to a dramatic increase in volume of telemedicine echocardiograms, with no significant differences in efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 25 publications
1
23
0
1
Order By: Relevance
“…Antenatal management of high-risk pregnancies from a distance has been accomplished for conditions ranging from maternal diabetes, hypertensive disorders, cervical insufficiency, and suspected fetal anomalies, including congenital heart disease (90)(91)(92). In Arkansas, telemedicine-supported care in the rural setting has been shown to reduce the need for in-person visits (where the mother would have to travel to the tertiary center) by nearly 50%, while maintaining the appropriate utilization of maternal-fetal medicine subspecialty consultations (91).…”
Section: Perinatal and Newborn Carementioning
confidence: 99%
“…Antenatal management of high-risk pregnancies from a distance has been accomplished for conditions ranging from maternal diabetes, hypertensive disorders, cervical insufficiency, and suspected fetal anomalies, including congenital heart disease (90)(91)(92). In Arkansas, telemedicine-supported care in the rural setting has been shown to reduce the need for in-person visits (where the mother would have to travel to the tertiary center) by nearly 50%, while maintaining the appropriate utilization of maternal-fetal medicine subspecialty consultations (91).…”
Section: Perinatal and Newborn Carementioning
confidence: 99%
“…Krishnan et al 45 reported the technology transition at a single center with >10 000 telemedicine transmissions from 24 sites in 7 states and territories between 2001 and 2012. Abnormalities were detected in >40% of the studies, including >100 patients with life-threatening defects.…”
Section: Evolution Of the Technologymentioning
confidence: 99%
“…Telemedicine has the potential to alter the equation. Although no data have been published that suggest telemedicine will increase the use of echocardiography, 30,45 the potential for this to happen certainly exists. Additionally, telemedicine could decrease the need of pediatric cardiologists in more remote areas, allowing tertiary care centers to hire more cardiologists, who can then provide echocardiography interpretation remotely.…”
Section: Workforce and Trainingmentioning
confidence: 99%
“…Although beneficial to patient care, flexibility is a limitation. The advent of the Internet and wireless communication enabled versatile, low cost, and rapid transmission between multiple access points, which was revolutionary for telemedicine . Increased Internet bandwidth enabled the faster transmission of larger stored image files and real‐time transmission of video files of higher image quality and frame rate .…”
Section: Historical Perspective and Future Directionsmentioning
confidence: 99%
“…If an immediate discussion is not needed, stored or captured videos and still image files or connecting hyperlinks can be shared. This capture and send approach to sharing images allows the recipient to continue with the current clinical work and review the sent information later …”
Section: Introductionmentioning
confidence: 99%